2003
DOI: 10.1016/s1096-7176(02)00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux analysis of xylose metabolism in recombinant Saccharomyces cerevisiae using continuous culture

Abstract: This study focused on elucidating metabolism of xylose in a Saccharomyces cerevisiae strain that overexpresses xylose reductase and xylitol dehydrogenase from Pichia stipitis, as well as the endogenous xylulokinase. The influence of xylose on overall metabolism was examined supplemented with low glucose levels with emphasis on two potential bottlenecks; cofactor requirements and xylose uptake. Results of metabolic flux analysis in continuous cultivations show changes in central metabolism due to the cofactor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 48 publications
(52 reference statements)
6
71
0
4
Order By: Relevance
“…In contrast to the expression in C1, the levels of expression of genes involved in glycolysis, redox metabolism, and ethanol or glycerol production were not altered in TMB3400, which may explain why this mutant cannot grow anaerobically on xylose alone (49). Our conclusion that increased cytosolic NADPH formation and NADH consumption are important for anaerobic growth of yeast on xylose is consistent with flux and proteome data obtained for recombinant, xylose-fermenting S. cerevisiae during a shift from glucose-containing medium to glucose-xylosecontaining medium (26,31). In particular, it was shown that strains overexpressing the preferentially NADPH-dependent xylose reductase from P. stipitis generate the required NADPH primarily through the oxidative pentose phosphate pathway (16).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the expression in C1, the levels of expression of genes involved in glycolysis, redox metabolism, and ethanol or glycerol production were not altered in TMB3400, which may explain why this mutant cannot grow anaerobically on xylose alone (49). Our conclusion that increased cytosolic NADPH formation and NADH consumption are important for anaerobic growth of yeast on xylose is consistent with flux and proteome data obtained for recombinant, xylose-fermenting S. cerevisiae during a shift from glucose-containing medium to glucose-xylosecontaining medium (26,31). In particular, it was shown that strains overexpressing the preferentially NADPH-dependent xylose reductase from P. stipitis generate the required NADPH primarily through the oxidative pentose phosphate pathway (16).…”
Section: Discussionsupporting
confidence: 90%
“…NADH/NAD + and NADPH/NADP ratios, are important markers when considering strategies for metabolic engineering of an organism (Moreira dos Santos et al, 2003;Pitkanen et al, 2003;Thomas et al, 2007). In particular, increased redox potential is considered as an important factor in improving BDO production in (Zhuang et al, 2013).…”
Section: Redox Potential Considerationsmentioning
confidence: 99%
“…Thus, low, but non-zero, concentration of glucose enhances xylose metabolism. The effect has been attributed to improved co-factor generation [22] and the induction of genes for transporter systems [22] and glycolytic enzymes [23].…”
Section: Introductionmentioning
confidence: 99%